2009
DOI: 10.1002/art.24492
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of lipid profile is accompanied by atheroprotective alterations in high‐density lipoprotein composition upon tumor necrosis factor blockade: A prospective cohort study in ankylosing spondylitis

Abstract: Objective. Cardiovascular mortality is increased in ankylosing spondylitis (AS), and inflammation plays an important role. Inflammation deteriorates the lipid profile and alters high-density lipoprotein cholesterol (HDL-c) composition, reflected by increased concentrations of serum amyloid A (SAA) within the particle. Anti-tumor necrosis factor (anti-TNF) treatment may improve these parameters. We therefore undertook the present study to investigate the effects of etanercept on lipid profile and HDL compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 37 publications
6
50
0
Order By: Relevance
“…76 In patients with AS, 77,78 although significant increase in HDL was reported, the TC to HDL ratio remained unchanged. 77 Meanwhile, apo B to apo A ratio decreased significantly. 77 Three studies analyzed patients with mixed inflammatory arthritis also showed inconsistent or even contradictory results.…”
Section: Mechanism Of Inflammation In Cvd In Inflammatorymentioning
confidence: 98%
See 2 more Smart Citations
“…76 In patients with AS, 77,78 although significant increase in HDL was reported, the TC to HDL ratio remained unchanged. 77 Meanwhile, apo B to apo A ratio decreased significantly. 77 Three studies analyzed patients with mixed inflammatory arthritis also showed inconsistent or even contradictory results.…”
Section: Mechanism Of Inflammation In Cvd In Inflammatorymentioning
confidence: 98%
“…77 Meanwhile, apo B to apo A ratio decreased significantly. 77 Three studies analyzed patients with mixed inflammatory arthritis also showed inconsistent or even contradictory results. [79][80][81] Differences in the study population, follow-up duration, and anti-TNF agents (included IFX, ETN, and ADA) may be responsible for these discrepancies.…”
Section: Mechanism Of Inflammation In Cvd In Inflammatorymentioning
confidence: 98%
See 1 more Smart Citation
“…It is not yet established that all modes of antiinflammatory action mediate similar magnitudes of change in lipid metabolism for a given change in systemic inflammation levels. Moreover, the picture becomes even more complex in RA, where there is evidence of 1) compositional changes in high-density lipoprotein (HDL) particles with inflammation (5) and 2) reversal of some of these changes with certain antiinflammatory therapies (6). Thus, interpretation of results that include data only on concentrations of, and not composition of, lipid particles is challenging, and elucidation of likely net effects on CVD risk in the context of an "inflammation-lipid paradox" is hazardous.…”
mentioning
confidence: 99%
“…[194][195][196] Similar beneficial effects of etanercept treatment on the lipid profile were observed in patients with ankylosing spondylitis. 197 The detailed interplay of the proinflammatory activity of TNF-α with insulin resistance and lipid metabolism in the context of atherosclerosis and cardiometabolic disorders thus warrants further investigation.…”
mentioning
confidence: 99%